Arthroscopic-guided Release of Supraspinatus and Infraspinatus Muscles for Repair of Large-to-Massive Rotator Cuff Tear and Suprascapular Nerve Release - Kyu-Cheol Noh, M.D., Ph.D.; Jun Lang, M.D.; Ji-Ung Oh, M.D.; Yong-Tae Kim, M.D., Ph.D.; Vivek Kumar Morya, Ph.D. (Arthroscopy Techniques)
This technical note presents an all-arthroscopic technique designed to release and advance the supraspinatus and infraspinatus muscles in cases of massive posterosuperior rotator cuff tears involving the retracted muscles. The aim is to avoid neuromuscular damage and facilitate tension-free repair by reducing the anatomical tendon footprint. Traditionally, such tears have been considered irreparable and have been treated with superior capsular reconstruction or tendon-transfer procedures. The all-arthroscopic approach detailed here involves muscle detachment and advancement, enhancing tendon mobilization, and enabling tension-free repair. The key to this technique is resection of the acromioclavicular joint to aid in muscle advancement, particularly for the supraspinatus muscle.